Digital Competence Assessment Survey for Language Teachers - Fominykh, Mikhail; Shikhova, Elizaveta; Soule, Maria Victoria; Perifanou, Maria; Zhukova, Daria (My University, 2021)
In this paper, we present the results of the digital competence assessment survey for language teachers. The survey assessed how language teachers use digital technologies, their attitude towards these technologies, their related skills and competencies, their satisfaction and training needs, and the institutional support they receive. In total, 283 language teachers from 43 countries participated in the survey. The data were collected in 2019. The results indicate that language teachers use various computer-assisted language learning instructional methods. They generally consider that digital technologies are beneficial for the classroom. The lack of training prevents them from using specific technology-based methodologies, in contrast to the lack of technical infrastructure. The majority of the participants are not satisfied with their level of digital language teaching expertise. Two-thirds of those who receive digital competency training at their organizations, report that the training sessions happen irregularly or rarely. At the same time, the majority of the teachers confirm these training to be effective and the skills they received are applied in practice. We discuss the results of the survey in relation to the previous research, policies and practical challenges of the digitalization of language education. The major contribution of the paper is a representation of the teacher’s perspective on the role of digital technologies in their practice. We assume that the new realia of teaching in the context of COVID-19 have changed the overall need in digital language teaching skills among the teachers, as well as the share of the teaching staff who teach online on a regular basis. The future work includes a new survey in order to evaluate the scope of this change.
Keywords: Digital competences; Language learning; Teacher education